The Use of Typology in Sociology - Di Gregorio, Marco; Simonella, Zenia (Italian Sociological Review, 2025)
This article presents an analysis of the manner in which typology is used, particularly in the field of sociology. Searching the Web of Science (WoS) database from 1990a random selection of 686 scientific articles was extracted from a total of 1173 in which the term typology appears. The authors then analysed the degree of conformity to the classic Aristotelian model and its variants, finding examples of terminological confusion as well as errors of a semantic or gnoseological nature. The results of the analysis show that the classic Aristotelian typology continues to be present in the scientific journals, even if an increasing tendency can be seen towards an “extensional” method of construction through the use of multivariate techniques of analysis. Almost half of the sample considered displays incorrect uses of the term, or errors where other conceptual objects (classifications, taxonomies, classes, types and taxa) are identified with typology. Such errors were found even in articles published in journals considered of high prestige. The authors conclude that typology, with the heuristic advantages it offers, continues to constitute an important tool for the social scientist and that criticism or distrust directed at it often derive from inadequate cognizance or from misguided attempts to equate the spheres of thought, of language and of reality.